ANÁLISE DA PRODUÇÃO CIENTÍFICA DO CURSO DE NUTRIÇÃO DA UNIVERSIDADE FEDERAL DE MATO GROSSO - Tarsis de Mattos Maia; Lorena Barbosa Fonseca; Emanuele Batistela; Raquel Azambuja Reinaldo; Luana Pucci de Lima; Maria Aparecida de Lima Lopes (Universidade do Estado do Rio de Janeiro, 2015)
The Nutrition course at the Federal University of Mato Grosso,Brazil, was created in 1978 and implemented in 1979, growinggradually and slowly in its early years. This study aimed toevaluate the scientific production of the course over thirtyyears, since its creation. Data were collected online from theLattes curriculum of active and retired teachers of the course.The survey identified significant increase in the total numberof publications during the investigated period (1981-2011). Mostof the publications (52.6%) consisted of abstracts published inconference proceedings, and the period 2001-2011 showed thehighest scientific production, either by diversity of type or byquantity of production. The three thematic areas that prevailedduring the studied period are related to the biological nature ofresearch in nutrition, namely Basic and Experimental Nutrition,followed by Food Science and Technology and Clinical Nutrition,the latter sharing space with the field of Nutritional Assessment ofPopulations. Although inserted in the national context, the resultsare limited to the course, and it is not possible to extrapolatethem or make conclusions about them, since they are part of thehistorical construction of the UFMT Nutrition course. Furtherstudies should be made considering the small number of currentstudies, the analysis of scientific literature and way of publicationson the national context. DOI: 10.12957/demetra.2015.14870